Analysis Of Students’ Errors in Solving AKM Problems Perimeter and Area of Flat Shape - Tri Wahyuni, Yeni; Sari Rufiana, Intan; Faizah, Siti; Rizki Kusumaningrum, Shirly; Sukma Indra Dewi, Radeni (University of Muhammadiyah Malang, 2024)
Numeration in AKM, which is contextualized in various types of questions, aims to evaluate student competence. So, it is necessary to know where students' mistakes are to improve how students solve mathematical problems. This research aims to describe students' mistakes in solving problems on AKM questions related to the perimeter and area of ​​flat shapes. This research is descriptive qualitative research. The research subjects chosen in this study were based on consideration of students' mathematical ability test results in the high (80 to 90), medium (65 to 80), and low (less than 65) categories. Then, three students were randomly selected for each ability level, with details: 1 student with high ability, 1 with medium ability, and 1 with low ability. The data collection techniques used in this research aretests, interviews, and documentation. Data analysis techniques used in the Miles and Huberman model can help understand problems well and plan problem-solving systematically. Students who are in the low category are not yet able to fulfill every indicator of solving mathematical problems and are not able to solve the problems given correctly.